Managing complications of radiation therapy in head and neck cancer patients: part IV. management of osteoradionecrosis - Ramli, R.; Ngeow, Wei Cheong; Rahman, R.A.; Chai, Wen Lin (2006)
Head and neck cancer is becoming a more recognizable pathology to the general population and dentists. The modes of treatment include surgery and/or radiation therapy. Pretreatment dental assessment should be provided for these patients before they undergo radiation therapy. There are occasions, however, whereby head and neck cancer patients are not prepared optimally and, as a result, they succumb to complicated oral adverse effects after radiation therapy. Osteoradionecrosis (ORN) is a severe debilitating condition that impairs healing due to reduction in vascularity and osteocyte population in the affected bone. This article reviews methods of treatment used to treat ORN such as antibiotics, hyperbaric oxygen therapy, therapeutic ultrasound, surgery, and other modalities.